Multi-Parameter Analysis of Biosignals in Long-Term Control Medical Devices Management - Holdobin, Serhii; Serhiienko, Olena; Brynza, Natalia; Sosnov, Ihor; Tiutiunyk, Olha; Samus, P. O. (IEEE, 2025)
The development of data processing technologies, microelectronics and sensor systems allows for high-precision multiparametric analysis of biosignals in real time. The paper considers the problem of automating medical processes to reduce the influence of the human factor and increase the accuracy of diagnostics. An improved method of multiparametric analysis of biosignals is proposed for long-term monitoring of the state of the cardiovascular system using modern sensor devices, data processing algorithms and artificial intelligence technologies. The research is aimed at improving the methods of collecting, transmitting and analyzing biosignals, which contributes to the creation of personalized medical devices and effective prediction of cardiovascular pathologies. The issues of classification of devices and biosignals, as well as their mathematical modeling to increase the accuracy of diagnostics, are considered.
Metadata, an abstract, a list of sources used, and a link to the text of the article are provided.
Keywords: multiparametric analysis; biosignals; cardiovascular system; long-term monitoring; artificial intelligence; sensor devices; diagnostic automation; machine learning; data processing algorithms; personalized medicine